A two-phase sonographic study among women with infertility who first had normal sonographic findings - Ochie, Kalu; C, Abraham John (Clinical Journal of Obstetrics and Gynecology, 2022)
Introduction: Sonographic scan tests are real-time procedures but the female reproductive systems are subject to continued changes beyond the mid-menstrual period. Therefore a second test may be useful after mid-menstrual ultrasound tests among women with infertility who first had normal ultrasound tests during the mid-menstrual period. Aim: The aim of this study is to find out whether physiological changes beyond the mid-menstrual period in the female reproductive system could develop into findings that could be missed at the first ultrasound test among women with infertility during mid menstrual period. Method: One hundred and forty (140) women participated in this study, over a period of 12 months. The inter-observer correlations were carried out. The ultrasound test measured the diameters of the endometrium and ovarian follicle. The study was carried out during the mid-menstrual cycle when normal changes are optimal. The subjects were women of childbearing age (18 years - 40 years) with 28 days cycles who were referred from the fertility clinic. Women who had previous pelvic surgery, women on fertility therapy, and women who were unsure of the date were excluded from the study. Only women who met the inclusion criteria were selected for the study. The selection was by convenience sampling method. The women underwent the first phase of the ultrasound test during the mid-menstrual cycle. Those who had ultrasonographic-positive infertility reports were returned to the referral clinic. Only women who had normal ultrasonographic fertility reports were included in the second phase of further ultrasonographic tests. The scans were carried out further for four days for this second phase study and the result was again compared with normal values. (Endometrium Normal range 7.4 mm - 13.5 mm and ovarian follicles normal range 17.4 mm to 23.5 mm). Results: The first phase of the scan showed 108 (77%) of the women had positive infertility results for endometrium and ovarian follicles, while 32 (23%) of the women had a normal ultrasonographic result and were rescanned over days. The findings of the second phase scan showed that 10 subjects (7.30%) showed new abnormalities, Findings were distributed in three sub-groups in this second phase of the study. Sub-group A, 4 (2.67%) had enlarged unruptured follicles, sub-group B, 6 (4.30%) had an endometrial cavity filled with fluid, sub-group C, 22 (15.70%) subjects still had normal scans who may be referred for other studies. Conclusion: Women with infertility who had a normal scan at the mid-menstrual cycle should be followed up with a second-phase ultrasound scan before other tests.